Efficacy of Ayurved based therapy on global longitudinal strain in ischemic heart disease: a retrospective analysis - Sane, Rohit; Ghadigaonkar, Pravin; Shelke, Gaurav; Singh, Raghvendra Pratap; Kulthe, Nilesh (International Journal of Research in Medical Sciences, 2024)
Background: The current study aimed to investigate the efficacy of the Ischemia Reversal program (IRP) as an Ayurveda based therapy to standard anti-ischemic therapy in patients with ischemic heart disease (IHD). Methods: A retrospective, single centre, observational study was conducted from January 2022 to May 2023. A total of 39 patients diagnosed with ischemic heart disease and global longitudinal strain (GLS) <15, regardless of underlying co-morbidities such as diabetes mellitus, hypertension, obesity, hyperlipidemia, low ejection fraction, history of myocardial infarction were included in this study. The primary endpoint was improvement in GLS from baseline to the 90-day follow-up in various different categories. Secondary endpoints were improvement in EF, abdominal girth, weight and reduction in dependency on allopathic medication from baseline to the 90-day follow-up. Results: The mean age of the study population was 59.23±9.01 years. Weight (day 1: 67.29±13.16 kg and day 90: 61.39±11.11 kg; p=0.00), body mass index (day 1: 25.75±4.03 and day 90: 23.79±3.50; p=0.00), abdominal girth (day 1: 95.31±10.75 cm and day 90: 85.67±17.02 cm p=0.00), EF (day 1: 40.74±10.30% and day 90: 53.91±11.87%; p=0.00), and GLS (day 1: -10.99±2.72 and day 90: -13.17±3.75; p=0.00) improved at the 90 day follow-up. Conclusions: The study showed notable improvements in weight, body mass index, abdominal girth, EF, and GLS after 90 days. These results suggest that IRP is beneficial treatment for IHD, but more extensive research is needed to confirm its effectiveness.